Paediatric radiation dose and cancer risk associated with body effective diameter during CT thorax examination. (November 2021) - Karim, M.K.A.; Harun, H.H.; Kayun, Z.; Aljewaw, O.B.; Azizan, S.H.N.; Rafiz, N.F.N.M.; Muhammad, N.A.
Abstract: Paediatric patients are considered vulnerable to radiation exposure and have a greater risk of developing radiation-induced cancers due to active growth cells. Radiation dose from a CT examination is the highest among other imaging modalities and can become harmful if unoptimised. Thus, the aim of this study is to evaluate the influence of paediatric size on SSDE value and to estimate cancer risk occurrence in specific organs of paediatric patients receiving CT chest examination. Data such as volume-weighted CT dose index (CTDIvol ), dose length product (DLP) and patient's demography were retrospectively collected from a 64-slice CT scanner (Siemens Somatom Definition AS+) at University Malaya Medical Centre. A total of 120 patients were categorised into four age groups: G1 (0 – < 1 years), G2 (1 – < 5 years), G3 (5 – < 10 years), and G4 (10 – < 15 years). SSDE value was estimate in accordance with the American Association of Physicists, 2011 in Medicine (AAPM) report 204. The effective dose (E) and SSDENCICT obtained from National Cancer Institute Dosimetry System (NCICT) were then compared to the conventional SSDE value. The highest value of CTDIvol, DLP and E were found in group G4 with 4.9 ± 2.5, 185.0 ± 140.8, and 4.2 ± 2.0, respectively. Moreover, there is only slightly different of SSDE value between the G1 and G2 groups with a factor of 0.91. No significant difference ( p > 0.05) was observed between the SSDEAAPM and SSDENCICT across all age groups. The cancer risk estimated shows thyroid organs receives the highest probability of cancer incidence in both the genders, which was calculated to be 2.1 for males and 3.9 for females per 100, 000 procedures, respectively. Nevertheless, adequate justification of paediatric CT scans and dose optimisation are required to reduce unnecessary exposure and radiation-induced risks. Highlights: Radiation dose such as effective dose and SSDE from paediatric CT chest examinations were evaluated. This study also estimates the cancer risk occurrence in selected organs of paediatric patients during CT chest examination. The highest dose was observed in higher age group where CTDIvol, DLP, and E is 4.9 ± 2.5, 185.0 ± 140.8, and 4.2 ± 2.0, respectively. The Thyroid organ received the highest probability of cancer incidence in both the genders.